THE EFFECT OF CHROMIC ACID CONCENTRATION ON THE FILM MORPHOLOGY, THICKNESS, AND CORROSION RESISTANCE OF ANODIZED ALUMINIUM 2024 â T3 IN CHROMIC ACID ANODIZING - Anggarine, Rizkynadifa
Aluminum 2024 is a material used in many applications, including aircraft components. One of the method to improve the corrosion resistance of aluminum is the anodizing process. In this study, the anodization process was carried out in chromic acid solution with concentrations of 48, 60, 70, and 80 g/L CrO3. The effect of varying chromic acid concentration during the anodization process on the thickness and morphology of the resulting aluminum oxide (AAO) layer was studied. The corrosion resistance of the AAO layer in 3.5% NaCl and 3.5% NaCl+100 ppm Na2SO4 solution was studied by electrochemical measurements such as Open Circuit Potential (OCP), potentiodynamic polarization, and Electrochemical Impedance Spectroscopy (EIS). The results showed that, the higher the concentration value of chromic acid, the thickness of the AAO coating increased from 3,6 mm to 5,3 mm. The corrosion resistance is also improved with the increase of chromic acid concentration. The OCP value of the oxide layer is more positive and the corrosion rate of the oxide layer obtained from the potentiodynamic polarization curve is decreasing, ranging from 0.057 mm/y to 0.0393 mm/y. Results obtained from EIS measurement do not align with the findings from OCP and potentiodynamic polarization. Therefore, further research needs to be conducted to deepen the understanding of the phenomenon.